The progress and challenges of circRNA for diabetic foot ulcers: A mini-review - Li, Deer; Guo, Jiaxing; Ni, Xiyu; Sun, Guanwen; Bao, Huhe (Frontiers in Endocrinology, 2022)
Since the Human Genome Project was successfully completed, humanity has entered a post-genome era, and the second-generation sequencing technology has gradually progressed and become more accurate. Meanwhile, circRNA plays a crucial role in disease regulation and its potential clinical application has gradually attracted the attention of physicians. However, the mechanisms of circRNA regulation at the cellular and molecular level of diabetic foot ulcer (DFU) is still not well-understood. With the deepening of research, there have been many recent studies conducted to explore the effect of circRNA on DFU. In this mini-review, we discuss the potential role of circRNA as a therapeutic target and diagnostic marker for DFU in order to gain a better understanding of the molecular mechanisms that underlie the development of DFU and to establish a theoretical basis for accurate treatment and effective prevention.